Analisis Pola Sebaran Area Upwelling di Selatan Indonesia Menggunakan Citra Modis Level 2 - I Gede Mita Anjas Swara; I Wayan Gede Astawa Karang; Gede Surya Indrawan (Journal of Marine Research and Technology, 2021)
This research aimed to find out the pattern of spasio-temporal upwelling and its relation with El Nino Southern Oscillation (ENSO) in the southern waters of Java to the East Nusa Tenggara. Two indicators namely sea surface temperature (SST) and chlorofil-a data obtained from oceancolor database were used as an indicator of upwelling occurences. The overlay technique and correlation analyses were used to describe the relationship between upwelling and ENSO. The results showed the phenomenon of upwelling occurred along southern Java and East Nusa Tenggara. The appearance of upwelling occurred in the South Easth Monsoon until transition season which began in June and ended in November. The pattern of upwelling area for 17 years varies each season, where for the South Easth Monsoon in June it gained 6986 km2, in July 78294 km2, and in August 254212 km2. As for transition season II in September 166767 km2, in October 72033 km2, and November 1949 km2. The results also showed that upwelling intensity was influenced by ENSO indicated by correlation values that matched the correlation value between SST - ENSO was -0.78 and chlorophyll-a-ENSO was 0.98.